2019
DOI: 10.1021/acsami.9b04649
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate-Incorporated Metallacalixarene@Graphene Composite Electrodes for High-Performance Supercapacitors

Abstract: Composites of polyoxometalate (POM)/metallacalixarene/graphene-based electrode materials not only integrate the superiority of the individual components perfectly but also ameliorate the demerits to some extent, providing a promising route to approach high-performance supercapacitors. Herein, first, we report the preparations, structures, and electrochemical performance of two fascinating POM-incorporated metallacalixarene compounds [Ag5(C2H2N3)6]­[H5 ⊂ SiMo12O40] (1) and [Ag5(C2H2N3)6]­[H5 ⊂ SiW12O40] (2); (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 71 publications
0
44
0
Order By: Relevance
“…[38,39] The electrochemically active surface area (ECSA) of Co-Ni MOF and its derivatives are also evaluated through the CV measurements at the potential window (0-0.1 V versus Hg/HgO) ( Figure S10, Supporting Information). [8,9,19] The specific electrical double layer capacitance (C dl ) of Co-Ni MOF, Co-Ni-B, Co-Ni-B-S, Co-Ni-S, and Co-Ni-S-B is 110.66, 45.8, 145.4, 48, and 2.5 F g −1 , respectively. It can be concluded that the ECSA of Co-Ni-B-S is much larger than that of the initial Co-Ni MOF electrode, suggesting their enhanced electrochemical performance in aqueous electrolyte, and authorizing the superiority of this structure.…”
Section: Doi: 101002/adma201905744mentioning
confidence: 99%
See 3 more Smart Citations
“…[38,39] The electrochemically active surface area (ECSA) of Co-Ni MOF and its derivatives are also evaluated through the CV measurements at the potential window (0-0.1 V versus Hg/HgO) ( Figure S10, Supporting Information). [8,9,19] The specific electrical double layer capacitance (C dl ) of Co-Ni MOF, Co-Ni-B, Co-Ni-B-S, Co-Ni-S, and Co-Ni-S-B is 110.66, 45.8, 145.4, 48, and 2.5 F g −1 , respectively. It can be concluded that the ECSA of Co-Ni-B-S is much larger than that of the initial Co-Ni MOF electrode, suggesting their enhanced electrochemical performance in aqueous electrolyte, and authorizing the superiority of this structure.…”
Section: Doi: 101002/adma201905744mentioning
confidence: 99%
“…Extensive energy demands by portable electronics and electric vehicles have indorsed the rapid development of highly efficient energy storage technologies for human society . Electrochemical capacitors (ECs) have received significant attention as a strong candidate in virtue of high power density, fast charging rate, and long‐term cyclability . Since the performance metrics and energy storage mechanism of ECs depend on the electrode materials, extensive investigations have been performed to optimize the structure and electronic valence of inorganic materials to improve the energy density …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the {Co 2 L 3 •6H 2 O} + , two Co 2+ metals, three L − molecules and six water molecules (Figure 1, (Figure 1, middle). [54][55][56][57] Moreover, the {Co 2 L 3 •6H 2 O} + clusters and adjacent GeMo 12 polyanions are integrated together through massive hydrogen bond interactions ( Figure S3, Supporting Information) to fabricate a 3D supermolecular structure ( Figure 1).…”
Section: Characterizations Of Polymer Precursor and Cos 2 @Mos 2 @Cc mentioning
confidence: 99%